Pengaruh Human Relations Terhadap Interaksi & Perilaku Remaja di Media Sosial - Yesya Vatria Barasa; Ayu Nurmala; Reva Fisalsabila; Deswita Fitriyani; Ariani Galuh Pangastuti; April Laksana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The advancement of information and communication technology has significantly altered the ways adolescents interact and establish social relationships, particularly through social media. This study aims to examine the impact of human relations on adolescents' interactions and behaviors on social media platforms, taking into account psychological, sociological, and cultural dimensions. Employing a qualitative approach with a literature review method, this research explores interaction patterns among adolescents on platforms such as Instagram, TikTok, and Twitter. The findings reveal that social media creates virtual spaces that enhance social networks but also pose risks such as reduced quality of face-to-face interactions, social anxiety, and mental health issues. This study emphasizes how the intense use of social media reshapes traditional communication patterns and influences adolescents' behavior and self-concept. Based on these findings, strategic recommendations are proposed for parents, educators, and policymakers to guide healthy social media use, balance its benefits and drawbacks, and foster the development of more meaningful social relationships among adolescents.